A resource unit integrating nutrition concepts and mathematical skills for Philippine high schools - Cabacoy, Teresita Poliquit
The primary purpose of this study is to develop a resource unit integrating nutrition with mathematics. It is intended for use in Philippine high schools. Utilized in the resource unit are two nutrition topics, viz., food nutrients and food allowances. These topics are used in the teaching of sets, deductive reasoning, constructions and interpretations of charts and graphs, and problem solving.